Human papillomavirus vaccine acceptance among adolescent girls in Ethiopia: a systematic review and meta-analysis - Amare Zewdie; Abebaw Wasie Kasahun; Adane Habtie; Anteneh Gashaw; Mulat Ayele (BMC, 2023)
Abstract Background Cervical cancer is the fourth most common cancer affecting females. Human papillomavirus vaccination of adolescent girls is the primary strategy for cervical cancer prevention but in Ethiopia, it lacks emphasis. Despite different studies done and found a highly variable level of vaccine acceptance; however, there was no summarized evidence on the issues as a nation. Thus this systematic review and meta-analysis aimed to assess the pooled prevalence of human papillomavirus vaccine acceptance by adolescent girls and its associated factors in Ethiopia. Method A systematic review and meta-analysis were conducted using PRISMA guidelines. Comprehensive literature was searched in PubMed, Google Scholar, and African Online Journal databases. A weighted inverse variance random effect model was used to estimate pooled prevalence. Cochrane Q-test and I2 statistics were computed to assess heterogeneity among studies. Funnel plot and Eggers test were done to assess publication bias. Review manager software was used to identify factors associated with vaccine acceptance. Result Overall, 157 articles were retrieved and finally 7 articles were included in this review. The pooled prevalence of adolescent human papillomavirus vaccine acceptance was 46.52% (95%CI; 30.47-62.57%). Subgroup analysis showed that adolescent vaccine acceptance was highest in the Oromia region and lowest in Addis Ababa. Knowledge about human papillomavirus vaccination (AOR = 3.89, 95% CI: (2.85-5.32)) and attitude (AOR = 2.65, 95% CI: (2.03- 3.44)) were significantly associated with adolescent's vaccine acceptance. Conclusion Human papillomavirus vaccine acceptance of adolescent girls in Ethiopia was low. Knowledge about the vaccine and attitude to vaccination were positively associated with their vaccine acceptance. Therefore, policymakers and program planners should target school-aged adolescents in increasing their awareness and changing their attitudes to enhance their vaccine acceptance in order to prevent and control cervical cancer.